Beyond HIV prevention: everyday life priorities and demand for PrEP among Ugandan HIV serodiscordant couples. Issue 1 (18th January 2019) - Nakku‐Joloba, Edith; Pisarski, Emily E; Wyatt, Monique A; Muwonge, Timothy R; Asiimwe, Stephen; Celum, Connie L; Baeten, Jared M; Katabira, Elly T; Ware, Norma C
Abstract: Introduction: Pre‐exposure prophylaxis (PrEP) to prevent HIV infection is being rolled out in Africa. The uptake of PrEP to date has varied across populations and locations. We seek to understand the drivers of demand for PrEP through analysis of qualitative data collected in conjunction with a PrEP demonstration project involving East African HIV serodiscordant couples. Our goal was to inform demand creation by understanding what PrEP means – beyond HIV prevention – for the lives of users. Methods: The Partners Demonstration Project evaluated an integrated strategy of PrEP and antiretroviral therapy (ART) delivery in which time‐limited PrEP served as a "bridge" to long‐term ART. Uninfected partners in HIV serodiscordant couples were offered PrEP at baseline and encouraged to discontinue once infected partners had taken ART for six months. We conducted 274 open‐ended interviews with 93 couples at two Ugandan research sites. Interviews took place one month after enrolment and at later points in the follow‐up period. Topics included are as follows: (1) discovery of serodiscordance; (2) decisions to accept/decline PrEP and/or ART; (3) PrEP and ART initiation; (4) experiences of using PrEP and ART; (5) PrEP discontinuation; (6) impact of PrEP and ART on the partnered relationship. Interviews were audio‐recorded and transcribed. We used an inductive, content analytic approach to characterize meanings of PrEP stemming from its effectiveness for HIV prevention. Relevant content was represented as descriptive categories. Results: Discovery of HIV serodiscordance resulted in fear of HIV transmission for couples, which led to loss of sexual intimacy in committed relationships, and to abandonment of plans for children. As a result, partners became alienated from each other. PrEP countered the threat to the relationship by reducing fear and reinstating hopes of having children together. Condom use worked against the re‐establishment of intimacy and closeness. By increasing couples' sense of protection against HIV infection and raising the prospect of a return to "live sex" (sex without condoms), PrEP was perceived by couples as solving the problem of serodiscordance and preserving committed relationships. Conclusions: The most effective demand creation strategies for PrEP may be those that address the everyday life priorities of potential users in addition to HIV prevention. Clinical Trial Number: NCT02775929